Mascot Design as a Branding Strategy for Serayu River, Kaliori Village, Banyumas Regency - Luqman Wahyudi; Ratih Alifah Putri; Famila Dwi Winati; Gilang Ramadhan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Kaliori Village, located in Banyumas Regency, Central Java, is renowned for its rich arts and culture. Despite its cultural prominence, certain local potentials, such as the Serayu River, remain underdeveloped as tourism assets. This study aims to design a mascot as a branding strategy to enhance the Serayu River's image and promote it as a tourist destination. The method used included consultation, field observation, and collaborative design processes involving local communities and stakeholders. Results show that the "Bebek Bawor" mascot effectively embodies the cultural identity of Banyumas and contributes to increased brand awareness through its application in promotional materials and strategic placements. The conclusion highlights the significance of integrating cultural representation with modern branding techniques to develop sustainable tourism while fostering community participation.